Knowledge, attitudes, and practices of caregivers of functionally disabled older adults regarding nutritional management - Jia, Jing; Guo, Ying; Tian, Li; Li, Wen; Cao, Xianyan; Shang, Yanping (Frontiers in Nutrition, 2025)
ObjectiveThis study aimed to assess the knowledge, attitudes, and practices (KAP) of caregivers of functionally disabled older adults regarding nutritional management.MethodsA multicenter cross-sectional survey was conducted on caregivers of functionally disabled older adults between April and June 2025 across Guangdong, Guangxi, and Hunan Province, utilizing an online questionnaire to collect demographic information and evaluate knowledge and practice scores. In this study, caregiver burden measured by the Zarit Burden Interview Short Form (ZBI-12) was defined as the attitudinal construct within the KAP framework. Structural equation model (SEM) was constructed to evaluate the interrelationships among the KAP.ResultsA total of 550 valid responses were included, yielding an effective response rate of 86.21%. The majority of respondents were female (71.09%). The mean knowledge, attitude, and practice scores were 15.30 ± 6.23 (possible range: 0–24), 18.53 ± 10.01 (possible range: 0–48), and 33.44 ± 7.01 (possible range: 9–45), respectively. SEM indicated significant associations from knowledge to attitude (β = −0.478, p = 0.015) and practice (β = 0.589, p = 0.018), and from attitude to practice (β = −0.286, p = 0.011). In addition, knowledge showed an indirect association with practice through attitude (β = 0.137, p = 0.007).ConclusionCaregivers of functionally disabled older adults demonstrated limited knowledge, moderate attitudes, and proactive practices in nutritional management. Intervention strategies should prioritize targeted educational support that enhances caregivers’ nutritional knowledge while simultaneously addressing attitudinal barriers and caregiver burden to optimize caregiving behaviors.